Modular Endoprostheses for Nonneoplastic Conditions: Midterm Complications and Survival. (5th December 2016) - De Gori, Marco; Scoccianti, Guido; Frenos, Filippo; Bettini, Leonardo; Familiari, Filippo; Gasparini, Giorgio; Beltrami, Giovanni; Cuomo, Pierluigi; De Biase, Pietro; Capanna, Rodolfo
Abstract : The use of modular endoprostheses is a viable option to manage both tumor resection and severe bone loss due to nonneoplastic conditions such as fracture sequelae, failed osteoarticular grafts, arthroplasty revisions, and periprosthetic fractures. We sought to investigate both midterm complications and failures occurred in 87 patients who underwent a megaprosthetic reconstruction in a nonneoplastic setting. After a mean follow-up of 58 (1–167) months, overall failure-free survival was 91.5% at 1 year, 80% at 2 years, 71.6% at 5 years, and 69.1% at 5 and 10 years. There was no significant difference in the survival rate according to the diagnosis at the index procedure (p = 0.921 ), nor to the reconstruction site (p = 0.402 ). The use of megaprostheses in a postneoplastic setting did not affect survival rate in comparison with endoprosthetic reconstruction of pure nonneoplastic conditions (p = 0.851 ). Perimegaprosthetic infection was the leading complication, occurring in 10 (11.5%) patients and implying a megaprosthetic revision in all but one case. Physicians should consider these results when discussing with patients desired outcomes of endoprosthetic reconstructions of a nonneoplastic disease.